2004
DOI: 10.1007/s00426-003-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial interference and response control in sequence learning: the role of explicit knowledge

Abstract: In several sequence learning studies it has been suggested that response control shifts from the stimuli to some internal representation (i.e., motor program) through the learning process. The main questions addressed in this paper are whether this control shift is related to explicit knowledge and whether the formation of these internal representations depends on the stimulus attributes. In one experiment we compared the learning of a response sequence triggered by either spatial location or location symbol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 32 publications
6
33
0
Order By: Relevance
“…Curran and Keele showed stronger learning effects for more aware than for less aware participants; that is, reaction time decreased across repetitions more drastically for more aware participants. Such results have been replicated in several studies (e.g., Hoffman & Koch, 1997;Koch, 2007;Tubau & López-Moliner, 2003;Willingham et al, 1989), although a few studies have shown no difference between aware and unaware participants (see Marcus, Karatekin, & Markiewicz, 2006;Stadler, 1995).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Curran and Keele showed stronger learning effects for more aware than for less aware participants; that is, reaction time decreased across repetitions more drastically for more aware participants. Such results have been replicated in several studies (e.g., Hoffman & Koch, 1997;Koch, 2007;Tubau & López-Moliner, 2003;Willingham et al, 1989), although a few studies have shown no difference between aware and unaware participants (see Marcus, Karatekin, & Markiewicz, 2006;Stadler, 1995).…”
mentioning
confidence: 71%
“…On the one hand, the finding that anticipation duration is modulated by awareness is in line with the results of studies using the SRT task. Indeed, several studies using the SRT task showed that participants aware of the repetition had stronger learning effects than did participants unaware of the repetition (Curran & Keele, 1993;Hoffman & Koch, 1997;Koch, 2007;Tubau & López-Moliner, 2003;Willingham et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies in adults indicate that diVerent brain regions are involved in sequence learning depending on the nature of the stimuli (Robertson, Tormos, Maeda, & Pascual-Leone, 2001). Behavioral and lesion studies further suggest that separable mechanisms are involved in learning spatial versus nonspatial sequences (Koch & HoVmann, 2000;Mayr, 1996), and spatial versus stimulus-response regularities in spatial sequences (Helmuth et al, 2000), and that nonspatial stimulus sequences lead to greater explicit awareness than do spatial stimuli (Tubau & Lopez-Moliner, 2004).…”
Section: Limitsmentioning
confidence: 98%
“…(pp. 1231-1232) In discussions of eye movements on the SRT task, eye movements are often referred to as responses (e.g., Mayr, 1996;Tubau & López-Moliner, 2004). The present results challenge this view.…”
Section: Implications For Research On Sequence Learningmentioning
confidence: 99%